2013
DOI: 10.3889/oamjms.2013.002
|View full text |Cite
|
Sign up to set email alerts
|

Visceral Fat Cut-off Points for a Sample of Egyptian Adults

Abstract: Objective: To determine appropriate visceral fat cut-off values using ultrasound (USVF); for obesity according to existing waist circumference (WC), waist/hip ratio (WHR) and BMI cut-off levels.Methods: 998 Egyptian adults, aged 25-55 years, were studied in a cross-sectional survey for evaluation of "Visceral and Central Obesity as an Early Estimator for Obesity Health Risk". Results:Using WC as standard for classification of central obesity, cut-off points of USVF were found to be 6.5 cm for men and 5 cm for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…General obesity was defined by body mass index (BMI) of ≥30 kg/ m 2 and overweight was defined by BMI greater than or equal to 25 kg/m 2 . Central obesity was determined using four measures: WC >94 cm for men and >80 cm for women, WHR >0.90 for men and >0.85 for women [10], and VFT > 6.5 cm for men and >5 cm for women and SCFT >1.5 cm [22,23]. Normal-weight central obesity using WC as a measure is defined as having a normal BMI and WC >94 cm for men and >80 cm for women.…”
Section: Cut-off Points For Obesitymentioning
confidence: 99%
“…General obesity was defined by body mass index (BMI) of ≥30 kg/ m 2 and overweight was defined by BMI greater than or equal to 25 kg/m 2 . Central obesity was determined using four measures: WC >94 cm for men and >80 cm for women, WHR >0.90 for men and >0.85 for women [10], and VFT > 6.5 cm for men and >5 cm for women and SCFT >1.5 cm [22,23]. Normal-weight central obesity using WC as a measure is defined as having a normal BMI and WC >94 cm for men and >80 cm for women.…”
Section: Cut-off Points For Obesitymentioning
confidence: 99%
“…The research findings align with a previous investigation conducted by Ramli et al (2018) Malaysian study, which found that 12.3% of participants had osteoporosis and 28.0% of participants had osteopenia, were consistent with our findings. However, Hassan et al, (2020) study in Egypt on the early identification of osteoporosis in premenopausal Egyptian women revealed that 47% of the participants in the study had normal weight and bone density, 42.5% had osteopenia, and 10.2% had osteoporosis. Regarding the relationship between the stu dy's female participants' demographics and their overall level of osteoporosis knowled ge.…”
Section: Discussionmentioning
confidence: 94%
“…Even though conversion factors are being developed, this currently limits the usefulness of echo intensity reference values. Furthermore, it would appear that there is a lack of universally accepted cut‐offs for intra‐abdominal fat thicknesses, with different cut‐offs proposed for various risks . Therefore, further work is required to validate USS measurements and to develop universally agreed reference data, which is cognisant of age, sex and ethnicity.…”
Section: Ultrasound Scanningmentioning
confidence: 99%